Tuning Thalamic Firing Modes via Simultaneous Modulation of T- and L-Type Ca2+ Channels Controls Pain Sensory Gating in the Thalamus - Cheong, Eunji; Lee, Sukchan; Choi, B. Jiwon; Sun, Minjeong; Lee, C. Justin; Shin, Hee-Sup (SOC NEUROSCIENCE, 2008)
Two firing modes of thalamocortical (TC) neurons, tonic and burst firings, are thought to reflect the divergent states of sensory signal transmission from the thalamus to the cortex. However, the behavioral consequences of changes in the thalamic firing between the two modes have not been well demonstrated. Moreover, although the firing modes of TC neurons are known to be affected by corticothalamic inputs via thalamic metabotropic glutamate receptor type 1 (mGluR1)-phospholipase C beta 4 (PLC beta 4) pathway, its molecular mechanisms have not been well elucidated. We addressed these questions using PLC beta 4-deficient mice, which show decreased visceral pain responses. We demonstrate that burst and tonic firings of TC neurons are concomitantly regulated by PLC beta 4 pathway. Blocking of this pathway by the mutation simultaneously increases bursting and decreases tonic firing of TC neurons through concurrent upregulation of T- and L-type Ca2+ currents. The mice with increased bursting and decreased tonic firing of TC neurons showed reduced visceral pain responses. Furthermore, we show that modulation of the Ca2+ channels or protein kinase C (PKC), a downstream molecule of PLC beta 4, altered the firing modes of TC neurons and pain responses in the predicted ways. Our data demonstrate the molecular mechanism and behavioral consequences of altered firing modes of TC neurons in relaying the visceral pain signals. Our study also highlights the thalamic PLC beta 4-PKC pathway as a "molecular switch" for the firing modes of TC neurons and thus for pain sensory gating.
Keywords: METABOTROPIC GLUTAMATE-RECEPTOR; CA2+-ACTIVATED K+ CHANNELS; LATERAL GENICULATE-NUCLEUS; HIPPOCAMPAL-NEURONS; CALCIUM-CHANNELS; MICE LACKING; SOMATOSENSORY CORTEX; ABSENCE SEIZURES; MESSENGER-RNA; RELAY NEURONS